Gods of play : baroque festive performances as rhetorical discourse - Aercke, Kristiaan, 1959- (SUNY series, the margins of literature., 1994)
This book studies the close connections between politics, culture, art, and philosophy in seventeenth-century Europe. As an emblem of this interrelationship, the author has chosen the phenomenon of the 'splendid festive performance' of spectacular plays and operas given at absolutist courts in Rome, Madrid, Paris, Versailles, and Vienna between 1631 and 1668. Gods of Play fills voids in the scholarly literature on the seventeenth-century, on absolutism, on courtly theatricality, and on the philosophy of play. Aercke demonstrates that such splendid performances were not just frivolous entertainment for the courtly class but were serious activities with far-ranging political consequences.